Content congruency and its interplay with temporal synchrony modulate integration between rhythmic audiovisual streams - Su, Yi-Huang (Frontiers in Integrative Neuroscience, 2014)
Both lower-level stimulus factors (e.g., temporal proximity) and higher-level cognitive factors (e.g., content congruency) are known to influence multisensory integration. The former can direct attention in a converging manner, and the latter can indicate whether information from the two modalities belongs together. The present research investigated whether and how these two factors interacted in the perception of rhythmic, audiovisual streams derived from a human movement scenario. Congruency here was based on sensorimotor correspondence pertaining to rhythm perception. Participants attended to bimodal stimuli consisting of a humanlike figure moving regularly to a sequence of auditory beat, and detected a possible auditory temporal deviant. The figure moved either downwards (congruently) or upwards (incongruently) to the downbeat, while in both situations the movement was either synchronous with the beat, or lagging behind it. Greater cross-modal binding was expected to hinder deviant detection. Results revealed poorer detection for congruent than for incongruent streams, suggesting stronger integration in the former. False alarms increased in asynchronous stimuli only for congruent streams, indicating greater tendency for deviant report due to visual capture of asynchronous auditory events. In addition, a greater increase in perceived synchrony was associated with a greater reduction in false alarms for congruent streams, while the pattern was reversed for incongruent ones. These results demonstrate that content congruency as a top-down factor not only promotes integration, but also modulates bottom-up effects of synchrony. Results are also discussed regarding how theories of integration and attentional entrainment may be combined in the context of rhythmic multisensory stimuli.